Modeling the Potential of Wind Power Plants in Kupang Regency Based on Weighted Overlay and Remote Sensing - Fadilah, Muhamad Fauzan; Sulastri, Ai; Firmansyah, Rahman; Algifahri, Fikri (PT. Pubsains Nur Cendekia, 2025)
Kupang Regency has significant wind energy potential, offering opportunities for wind farm development to address electricity shortages and support the transition to green energy. This study aims to analyze the wind energy potential in Kupang Regency for wind farm development. The weighted overlay method used integrates various criteria to determine the feasibility of recommended locations. Parameters such as wind speed, elevation, and land use were processed using Geographic Information Systems (GIS) technology. The results indicate that the southern and northern regions of Kupang Regency are optimal for wind farm development, considering high wind speeds (6 m/s), suitable land use (shrublands or sandy areas), and favorable elevation (highlands). The integrated analysis identified moderately potential, potential, and very potential zones covering 108,734.20 ha, 53,391.24 ha, and 7,198.73 ha, respectively. These findings are expected to serve as a reference for effective renewable energy planning and help address the energy crisis in the region.